Pengaruh Pengetahuan Lingkungan Dan Sikap Peduli Limbah Terhadap Minat Mengolah Minyak Jelantah di Masyarakat Kota Medan - Irmawati br perangin angin; Farida Arisma; Laurena Ginting; Vina Gabriella Saragih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Public interest in processing household waste remains relatively low, including in the management of used cooking oil. In fact, proper waste management can provide significant environmental and economic benefits. The low level of public interest in processing used cooking oil is generally caused by a lack of environmental knowledge and a low attitude of concern toward waste management. This study aims to analyze the influence of environmental knowledge and waste-care attitudes on public interest in processing used cooking oil. The research employed a quantitative method involving 74 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that environmental knowledge and waste-care attitudes have a significant influence on public interest in processing used cooking oil. The simultaneous test also confirms a positive relationship among the three variables